Silver nanoparticles synthesized by the heavy metal resistant strain Amycolatopsis tucumanensis and its application in controlling red strip disease in sugarcane - Guerrero, Daiana Soledad (2022)
The production of bioethanol and sugar from sugarcane is an important economic activity in several countries. Sugarcane is susceptible to different phytopathogens. Over the last years, the red stripe disease caused by the bacterium Acidovorax avenae subsp. avenae produced significant losses in sugarcane crops. Bio-nanotechnology emerged as an eco-friendly alternative to the biosynthesis of antimicrobial molecules. The aims of this study were to (a) produce extracellular silver nanoparticles using the heavy metal resistant strain Amycolatopsis tucumanensis,(b) evaluate their antibacterial in vitro effect and (c) determine the potential of silver nanoparticles to protect sugarcane against red stripe disease. Amycolatopsis tucumanensis synthesized spherical silver nanoparticles with an average size of 35 nm. Nanoparticles were able to control the growth of A. avenae subsp. avenae in in vitro assays. In addition, in vivo assays in sugarcane showed a control upon the red stripe disease when silver nanoparticles were applied as preventivetreatment. The Disease Severity Index was 28.94% when silver nanoparticles were applied 3 days before inoculation with A. avenae subsp. avenae. To our knowledge, this is the first report of silver nanoparticles extracellularly synthesized by an Amycolatopsis strain that were able to inhibited the growth of A. avenae subsp. avenae and control the red stripe disease in sugarcane.